Dynamics and drivers of consumption and multidimensional poverty: Evidence from rural Ethiopia - Tilman Brück; Sindu Workneh Kebede (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This study aims to explore poverty measures, its dynamics and determinants using Multidimensional Poverty Index (MPI) and consumption poverty. Our results show that the two measures assign similar poverty status to about 52 percent of households and that both approaches confirm poverty is mainly transient in rural Ethiopia. However, we find that the trend in adjusted head count poverty is different when using these two poverty measures. In terms of determinants of poverty dynamics, we find that household size matters in consumption poverty while we do not find significant effects on multidimensional poverty. Amongst the shocks, drought shock is found to affect consumption poverty but not multidimensional poverty. This implies that short-term shocks are more reflected in consumption poverty while the effect of simultaneous shocks is exhibited significantly on multidimensional poverty. Overall, our result provides empirical evidence on the importance of using both measures as complementary to get a full picture of poverty measure, dynamics and determinants.
Keywords: I32; O12; 330; poverty dynamics; consumption; multidimensional poverty index; rural Ethiopia